The Provincial Supervisor Competency Dictionary - Kongka , Sathianrat (Arts of Management Journal, 2020)
The purposes of this study were (1) to identify the provincial supervisor competency; (2) to identify the provincial supervisor competency dictionary; and (3) to verify the provincial supervisor competency dictionary. A sample of 249 cases were drawn from the provincial supervisor in the Provincial Education Office, The Office of the Permanent Secretary Ministry of Education. This research design was non–experimental case design. The instruments included the semi-structured interview, the opinionnaire and the questionnaire for confirming the provincial supervisor competency dictionary. The statistics used to analyze the data were frequency, percentage, arithmetic mean, standard deviations, content analysis, and exploratory factor analysis. The research results were found as follows; The provincial supervisor competency was composed of 6 factors: (1) Academic Leadership (2) Teamwork (3) Accumulating Professional Task (4) Communication and Influencing (5) Human Potential Development and (6) Visioning The provincial supervisor competency dictionary consisted of 6 factors 53 competencies. They were listed as follows: (1) Academic Leadership with 15 competencies (2) Teamwork with 10 competencies (3) Accumulating Professional Task with 16 competencies (4) Communication and Influencing with 3 competencies (5) Human Potential Development with 4 competencies, and (6) Visioning with 5 competencies. The provincial supervisor competency dictionary was verified with accuracy, propriety, feasibility, and utility.